Brown planthopper: Nilaparvata lugens, resistance in rice cultivar IR64: mechanism and role in successful N. lugens management in central Luzon, Philippines - Cohen, Michael B.; Alam, Syed N.; Medina, Edith B.; Bernal, Carmencita C. (Wiley, 1997)
We investigated the mechanism of brown planthopper, Nilaparvata lugens (Stål), resistance in the popular rice cultivar IR64, and the current level of resistance of IR64 to N. lugens in a large rice growing area with low brown planthopper populations (Central Luzon, Philippines). In greenhouse experiments with N. lugens populations collected from Central Luzon, IR64 showed slight to moderate levels of antibiosis, antixenosis, and tolerance relative to the cultivars IR22 and Azucena, which contain no major genes for N. lugens resistance. IR64 was also more resistant than IR26 in most experiments, despite the fact that both varieties have the same major gene for N. lugens resistance, Bph1. This confirms that IR64 contains one or more additional, apparently minor, genes for brown planthopper resistance. Our findings also demonstrate that, in an area with low insecticide use, it is not necessary to have high levels of N. lugens resistance, even in a rice cultivar grown by the majority of farmers, to maintain low and stable N. lugens populations.